Dampak Bulliying terhadap Psikologi, Fisik, dan Sosial pada Siswa Sekolah Dasar - Fatur Rahman; Ichsan; Mohammad Riefyal Moulana; Zulfadli (Advances In Education Journal, 2025)
Bullying is a form of violence that often occurs in elementary schools and can have a serious impact on children's development. This study aims to identify the factors that influence the occurrence of bullying, its impact on the psychological, physical, and social aspects of elementary school students, and the handling efforts that can be done. This research uses a qualitative approach with a library research method. Data collection was conducted through documentation of written sources such as journal articles, books, and relevant research reports. Literature selection criteria included Indonesian-language articles published between 2020 and 2025 and listed on Google Scholar. A total of 10 articles were selected and analyzed in depth to obtain comprehensive information. The results showed that bullying has a significant impact on children's mental health such as anxiety, trauma, and post-traumatic stress (PTSD), as well as causing physical and social disorders such as injuries, social isolation, and decreased academic performance. In addition, it was found that environmental factors, individual character, and social relations also influence the occurrence of bullying. This study is expected to provide a deeper understanding of the impact of bullying among elementary school students and provide a basis for the development of more effective prevention and intervention strategies in the environment.